The effectiveness of the inclusion of sodium deoxyribonucleate in complex treatment of patients with community-acquired pneumonia - A. A. Zuikova; O. N. Krasnorutskaya; Yu. A. Kotova; N. V. Strakhova; D. Yu. Bugrimov (Лечащий Врач)
High degree of lethality, progressive increase of complications of community-acquired pneumonia (CAP), reduction of performance and formation of incapacitation make CAP an important medical and social problem. According to the modern concept of development of pulmonological service in Russia, for complex solution of the problem of high rate of CAP morbidity, it is necessary not only to develop questions of diagnostics and therapy, but also perfect methods of drug rehabilitation. The objective of the study was to assess clinical efficiency of inclusion of immunomodulator and repair in complex treatment of community-acquired pneumonia in patients with different degree of rehabilitation potential. The study was conducted on clinical bases of the chair of clinical therapy of FSBI of Voronezh region, Voronezh State Medical University named after N.N. Burdenko of the Ministry of Healthcare of Russia. In total, the study included 64 patients at the age of 18–55. It was defined that to assess the dynamics of CAP course, content of CD3, CD8, CD22 in blood, as well as concentration of IL-1, IL-8, IL-10 are the most significant in terms of diagnostics. The study results showed that, at the stage of rehabilitation, addition of sodium deoxyribonucleate in patients diagnosed with «CAP, I–II risk class (PSI)», to the standard therapy, gives more productive recovery of pulmonary tissue structures, as compared to the results in patients who got only standard therapy, normalizes most indicators of immune status, and pro-inflammatory cytokines, allowing to reduce the timelines of the patients’ temporary disability.